2020
DOI: 10.1016/j.sjbs.2020.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomics analysis of serum exosomein burn patients

Abstract: The exosome is an emerging concepts biomarkers due to their abnormal expression in various diseases. Research on exosome has already shifted from the laboratory to clinical application. This study uses bioinformatics technology to identify functional changes in proteins of serum exosomes from burn patients. A total of 231 quantifiable differentially-expressed proteins were screened out, 31 of them had statistically significant changes in expression levels. In the test group, expression of2 proteins had downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Clinical Specimens. Patients' blood was prepared to collect exosomes as recently described [25]. All serum specimens (MPP patients: n = 10; healthy: n = 10) were stored at -80 °C and further used for exosomes isolation.…”
Section: Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical Specimens. Patients' blood was prepared to collect exosomes as recently described [25]. All serum specimens (MPP patients: n = 10; healthy: n = 10) were stored at -80 °C and further used for exosomes isolation.…”
Section: Cellmentioning
confidence: 99%
“…Isolation and Identification of Serum Exosomes. This procedure was performed as recently described [25]. Briefly, serum exosomes were individually extracted from the healthy (n = 10) and patients (n = 10) with MPP with 10,000 × g for 30 min at 4 °C.…”
Section: Cellmentioning
confidence: 99%
“…In addition to cancer, MMRN1 is differentially expressed in other diseases including inflammation and bacterial and viral infections (186,(194)(195)(196)(197). Upregulation of MMRN1 has also been observed in injuries including septic shock-associated kidney injury (198) and in serum exosomes from burn patients (185). MMRN1 may also play a role in human pathogen interactions.…”
Section: Future Directions On the Functional Roles Of Mmrn1mentioning
confidence: 99%
“…Exosomes are able to promote metastasis [ 184 ], but how MMRN1 exosomal release is associated with cancer progression has not been investigated yet. Elevation of MMRN1 levels in serum exosomes has also been observed in burn patients [ 185 ] and patients with tuberculosis infection [ 186 ].…”
Section: Mmrn1 Protein Detection In Cancermentioning
confidence: 99%
“…Qin et al found that there was differential expression of 31 proteins in the serum exosomes of burn patients. Of particular note in their findings was the upregulation of ITGA2B and ITGB3 in the burn group, as these proteins act in the PI3K/AKT signaling pathway, which promotes cell proliferation and growth [ 253 ]. Wound healing, especially cutaneous, is critical in a burn patient, to restore the body’s barrier to fluid loss and infection.…”
Section: Exosomes and Their Cargo In Trauma-associated Complicationsmentioning
confidence: 99%